2019
DOI: 10.1103/physrevb.99.165103
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state of boron nitride combining computation, modeling, and experiment

Abstract: The equation of state (EOS) of materials at warm dense conditions poses significant challenges to both theory and experiment. We report a combined computational, modeling, and experimental investigation leveraging new theoretical and experimental capabilities to investigate warm-dense boron nitride (BN). The simulation methodologies include path integral Monte Carlo (PIMC), several density functional theory (DFT) molecular dynamics methods [plane-wave pseudopotential, Fermi operator expansion (FOE), and spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 139 publications
(162 reference statements)
4
42
0
Order By: Relevance
“…It is also interesting to note that we do not see a separate L shell ionization peak. We conclude that this shell is ionized gradually, as it occurs in dense carbon and boron materials [8,64,65,100]. Excitations of K shell electrons set in at 1.01 ×10 6 K, 37700 GPa, ρ/ρ 0 = 4.26, u p = 94.8 km/s and u s = 124 km/s.…”
Section: Discussionmentioning
confidence: 92%
“…It is also interesting to note that we do not see a separate L shell ionization peak. We conclude that this shell is ionized gradually, as it occurs in dense carbon and boron materials [8,64,65,100]. Excitations of K shell electrons set in at 1.01 ×10 6 K, 37700 GPa, ρ/ρ 0 = 4.26, u p = 94.8 km/s and u s = 124 km/s.…”
Section: Discussionmentioning
confidence: 92%
“…The general idea of our approach is to perform simulations along isochores at high temperatures (T 10 6 K) using PIMC and at low temperatures (T 10 6 K) using DFT-MD simulations. We find the two methods produce consistent results at overlapping temperatures [12,25].…”
Section: Methodsmentioning
confidence: 70%
“…We have constructed a consistent EOS of MgSiO 3 over a wide range of temperature and density conditions by combining results from DFT-MD and PIMC simulations in order to bridge the warm dense matter and plasma regimes [12,43]. One goal of performing high-precision computer simulations based on first principles is to guide the design of inertial confinement fusion (ICF) experiments under conditions where the K and L shell electrons are gradually ionized, which is challenging to predict accurately with analytical EOS models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also showed that purification methods using Chebyshev polynomials are equivalent to the use of Clenshaw-Curtis quadratures. This understanding led to a series of efficient algorithms using spectral quadratures [45,58] and applications to first-principles molecular dynamics [58,67,50].…”
Section: Introductionmentioning
confidence: 99%